Using the robotic platform in the therapy of multifocal ground glass opacities. Issue 2 (5th December 2022) - Udelsman, Brooks V.; Blasberg, Justin D.
Abstract: Due to their association with invasive adenocarcinoma, ground glass opacities that reach 3 cm in size, develop a solid component ≥2 mm on mediastinal windows, or exhibit ≥25% annual growth warrant operative resection. Minimally invasive techniques are preferred given that approximately one third of patients will present with multifocal focal disease and may require additional operations. A robotic‐assisted thoracoscopic surgical approach can be used with percutaneous or bronchoscopic localization techniques and are compatible with developing intraoperative molecular targeting techniques.